Understanding Emotional Engagement in Immersive VR Stress Management Programs - Kutsal , Ahmet; Turan , Selva (Health Nexus, 2025)
This study aimed to explore the dimensions of emotional engagement experienced by users participating in immersive virtual reality (VR) stress management programs. A qualitative phenomenological approach was employed to investigate how individuals emotionally interact with immersive VR environments designed for stress reduction. Nineteen participants from Turkey, who had completed VR-based stress management sessions within the past six months, were selected using purposive sampling. Data were collected through semi-structured, in-depth interviews and analyzed using a grounded theory approach across three stages: open coding, axial coding, and selective coding. NVivo 14 software was used for data management and coding. Theoretical saturation determined the final sample size. Thematic analysis revealed five core categories of emotional engagement: (1) emotional regulation and relief, characterized by feelings of calm, reduced anxiety, and emotional release; (2) immersive escape and containment, reflecting temporary psychological withdrawal and emotional safety; (3) reflective self-awareness, involving increased emotional insight and self-perception; (4) psychological safety and comfort, supported by sensory design and environmental predictability; and (5) affective transformation, encompassing mood elevation and deeper emotional shifts. Participants described immersive VR not only as a relaxation tool but as an emotionally rich environment capable of triggering introspection, affective balance, and transformation. Immersive VR stress management programs engage users across multiple emotional dimensions—physiological, cognitive, and affective. Emotional engagement is not a passive outcome but a dynamic and layered process shaped by presence, design features, and individual psychological factors. These findings underscore the importance of affect-sensitive design and implementation strategies in therapeutic VR, emphasizing the potential of immersive environments for promoting emotional resilience and mental well-being.